Erratum to “Branching and Bounding Criteria for the Asymmetric Travelling Salesman Problem” - Carpaneto, Giorgio; Toth, Paolo (Management Science, 1981)
Erratum to Carpaneto, Giorgio, Paolo Toth. 1980. Branching and bounding criteria for the asymmetric travelling salesman problem. Management Sci. 26 (7) 736–743.